Sustaining Unity Among Liberian Muslim Communities in Nigeria for Development - Dukuly, Omar Abdallah; Fofana, Abraham Abdurrahman (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
This study is motivated by the weakening sense of unity among Liberian Muslim communities in Nigeria, which affects their social engagement and contribution to community development. The main research problem revolves around identifying the supporting and hindering factors in sustaining Muslim unity within a diasporic context. The study aims to analyze the key drivers that strengthen unity among Liberian Muslims in Nigeria and to explore the major challenges that threaten their social and religious cohesion. A qualitative approach with a descriptive-analytical method was employed. Data were collected through in-depth interviews, participatory observation, and document analysis of community and religious activities. The findings reveal that shared religious identity, effective spiritual leadership, and solidarity rooted in ethnic and Islamic brotherhood (ukhuwah Islamiyah) serve as major sustaining factors. Conversely, differing religious orientations, leadership conflicts, and limited access to socio-economic resources emerge as significant obstacles. This research contributes to the understanding of socio-religious dynamics among African Muslim diasporas in Nigeria and offers insights for developing strategies to enhance social cohesion through Islamic values [Penelitian ini dilatarbelakangi oleh melemahnya semangat persatuan di kalangan komunitas Muslim Liberia di Nigeria, yang berdampak pada kurang optimalnya peran sosial dan kontribusi mereka terhadap pembangunan komunitas. Persoalan ini menimbulkan pertanyaan mengenai faktor-faktor yang menopang dan menghambat upaya menjaga kesatuan umat dalam konteks diaspora. Tujuan penelitian ini adalah untuk menganalisis faktor penopang persatuan komunitas Muslim Liberia di Nigeria serta mengidentifikasi tantangan utama yang dihadapi dalam menjaga solidaritas dan stabilitas sosial mereka. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif-analitik. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi terhadap berbagai aktivitas sosial dan keagamaan komunitas. Hasil penelitian menunjukkan bahwa faktor utama yang menopang persatuan adalah kesamaan identitas keagamaan, kepemimpinan spiritual yang efektif, serta solidaritas berbasis etnis dan nilai ukhuwah Islamiyah. Namun, tantangan utama meliputi perbedaan orientasi keagamaan, konflik internal kepemimpinan, dan keterbatasan akses terhadap sumber daya sosial-ekonomi. Penelitian ini berkontribusi dalam memperkaya kajian tentang dinamika sosial-keagamaan diaspora Muslim Afrika di Nigeria, serta memberikan dasar bagi formulasi strategi penguatan kohesi sosial berbasis nilai Islam.]